Mosaic IL6ST variant inducing constitutive GP130 cytokine receptor signaling as a cause of neonatal onset immunodeficiency with autoinflammation and dysmorphy. Issue 3 (30th January 2021) - Materna-Kiryluk, Anna; Pollak, Agnieszka; Gawalski, Karol; Szczawinska-Poplonyk, Aleksandra; Rydzynska, Zuzanna; Sosnowska, Anna; Cukrowska, Bożena; Gasperowicz, Piotr; Konopka, Ewa; Pietrucha, Barbara; Grzywa, Tomasz M; Banaszak-Ziemska, Magdalena; et al.
Abstract: Interleukin-6 signal transducer ( IL6ST ) encodes the GP130 protein which transduces the proinflammatory signaling of the IL6 cytokine family through Janus kinase signal transducers and activators of transcription pathway (JAK/STAT) activation. Biallelic loss-of-function IL6ST variants cause autosomal recessive hyper-IgE syndrome or a variant of the Stuve–Wiedemann syndrome. Somatic gain-of-function IL6ST mutations, in particular, small monoallelic in-frame deletions of which the most prevalent is the IL6ST Ser187_Tyr190del, are an established cause of inflammatory hepatocellular tumors, but so far, no disease caused by such mutations present constitutively has been described. Herein, we report a pediatric proband with a novel syndrome of neonatal onset immunodeficiency with autoinflammation and dysmorphy associated with the IL6ST Tyr186_Tyr190del variant present constitutively. Tyr186_Tyr190del was found by exome sequencing and was shown to be de novo (absent in proband's parents and siblings) and mosaic (present in approximately 15–40% of cells depending on the tissue studied—blood, urine sediment, hair bulbs and buccal swab). Functional studies were performed in the Epstein–Barr virus-immortalized patient's B cell lymphoblastoid cell line, which carried the variant in approximately 95% of the cells. Western blot showed that the patient's cells exhibited constitutive hyperphosphorylation of Tyr705 in STAT3, which is indicative of IL6-independent activation of GP130. Interestingly, the STAT3 phosphorylation could be inhibited with ruxolitinib as well as tofacitinib, which are clinically approved JAK1 and JAK3 (to lesser extent JAK2 and JAK1) inhibitors, respectively. Given our results and the recent reports of ruxolitinib and tofacitinib use for the treatment of diseases caused by direct activation of STAT3 or STAT1, we speculate that these drugs may be effective in the treatment of our patient's condition. Graphical Abstract: